Perceived distress, personality characteristics, coping strategies and psychosocial impairments in a national German multicenter cohort of patients with Crohn’s disease and ulcerative colitis - Petruo, Vanessa A.; Krauss, Ekaterina; Kleist, Anika; Hardt, Juliane; Hake, Karsten; Peirano, Julia; Krause, Thomas; Ehehalt, Robert; von Arnauld de la Perriére, Philipp; Büning, Jürgen; Treml, Oliver; Krauss, Norbert; Albrecht, Heinz; Felten, Gisela; Hermannspahn, Uta; Burkhardt, Ulrike; Eisold, Marc; Teich, Nils; Siegmund, Britta; Maaser, Christian; Bokemeyer, Bernd; Baumgart, Daniel C.; Neurath, Markus F.; Mudter, Jonas; German IBD Study Group (GISG) KND (Zeitschrift für Gastroenterologie, 2019)
Background and aims This study examined differences in personality, psychological distress, and stress coping in inflammatory bowel disease (IBD) depending on type of disease and disease activity. We compared patients suffering from Crohn’s disease (CD) and ulcerative colitis (UC) with controls. While the literature is replete with distinctive features of the pathogenesis of IBD, the specific differences in psychological impairments are not well studied.Methods In this German national multicenter study, participants were recruited from 32 centers. Two hundred ninety-seven questionnaires were included, delivering vast information on disease status and psychological well-being based on validated instruments with a total of 285 variables.Results CD patients were more affected by psychological impairments than patients suffering from UC or controls. Importantly, patients with active CD scored higher in neuroticism (p < 0.01), psychological distress (p < 0.001) and maladaptive stress coping (escape, p = 0.03; rumination, p < 0.03), but less need for social support (p = 0.001) than controls. In contrast, patients suffering from active UC showed psychological distress (p < 0.04) and maladaptive coping (avoidance, p < 0.03; escape, p = 0.01). Patients in remission seemed to be less affected. In particular, patients with UC in remission were not inflicted by psychological impairments. The group of CD patients in remission however, showed insecurity (p < 0.01) and paranoid ideation (p = 0.04).Conclusions We identified specific aspects of psychological impairment in IBD depending on disease and disease activity. Our results underscore the need for psychological support and treatment particularly in active CD.
Keywords: Crohn’s disease; ulcerative colitis; psychosocial distress